Authority, Subject and Object of the Dispute At the State Administrative Court (PTUN) - Sri Wahyuni; Arif Wibowo (JUSTICES: Journal of Law, 2023)
The State Administrative Court is established to anticipate the abuse of authority by the ruler and face conflicts of interest, disputes or disputes that may occur at any time between the community and state administrative agencies or officials. Therefore, this research is conducted to describe the authority, subject and object of dispute in the State Administrative Court using a library research or literature approach. Meanwhile, the approach method used is the normative juridical approach method or doctrinal legal research, which is a legal research whose data source comes from secondary data in the form of laws and regulations, books, and journals related to the focus of the problem. After discussing the existing problems, it can be concluded that  the competence of the State Administrative  Court includes absolute competence, namely the authority to adjudicate based on the object, material or subject matter of the dispute  and the relative competence, namely the authority to adjudicate based on the region or jurisdiction. The object   of disputes in the TUN Court is the TUN Decision except for TUN disputes within the TNI and other TUN disputes which according to the TUN Judicial Law are not the authority of the TUN Court where the exceptions are divided into 3 kinds of restrictions. i.e. direct, indirect and direct restrictions are temporary. Meanwhile, the ubjek of disputes in the TUN Court is a person or civil legal entity and a body or official  of TUN.